Decision Making for Highway Maintenance Using Fuzzy Logic (Case Study: The Aki Balak Street, Tarakan City) - M. Djaya Bakri; Eko Prihartanto (Institut Teknologi Sepuluh Nopember, 2017)
Highway is one of the facilities that is built to ease the transferring goods from one point to the destination. In the Law of the Republic of Indonesia No. 38 Year 2004 about road infrastructure, it is mentioned that the road has an important role in actualizing the development of nation’s life. Road repair by assessing the level of damage so that the researchers conducted this study on the Aki Balak street, Tarakan City with a road length observed along 250 meters. Types of road damage that occurred on the Aki Balak street consists of pothole, alligator cracking, long cracking, edge cracking, bledding, patching and corrugation. The results of the analysis using fuzzy logic applications in road maintenance as decision-making. An optimal decision making system in determining road maintenance from the damage and the causes of that damage occurred has been created. By using MATLAB student version, obtained extensive damage amounted 17.8 m2 with 9.99% condition assessment. Thus the results of routine maintenance at 2.5 with an appropriate alternative maintenance is repairing with flexible pavement, by providing an additional layer (overlay).